Assumptions essential for regression models building - Daoud, Jamal I. (Bandirma Onyedi Eylul University, 2025)
In regression analysis, most attention must be paid to assumptions about the regression model. One of the objectives of any regression model is to make inferences about the population's model for the same variables. Many assumptions must be tested before model building, while others must be tested after the model is obtained. All tests aim to find the best and most reliable model and make valid and useful inferences about the population parameters. These assumptions are defined, how to detect them, their impact on the model, and how to recover. This paper aims to raise awareness among researchers of the importance of meeting these assumptions, enhance the sense of good understanding of regression analysis and build the best models for the data subject of the study.